The b common (bc) family of cytokines, receptors and ligands - Lopez, Angel; Hercus, Timothy (Henry Stewart Talks, 2011)
Beta common cytokines, Excessive beta common cytokine function results in inflammatory diseases, Function through heterodimeric receptors, The alpha subunits have a conserved architecture, The beta subunit, Formation of a soluble GM-CSF receptor complex, Key interaction between cytokine and beta common, Site 2, Structure of soluble GM-CSF receptor complex, Crystal structure revealed a higher-order complex, Key dodecamer interactions are essential for receptor signalling, Knowledge of receptor activation mechanism contributes to inhibitor development
Updated at 2022/07/07